Salusins: Potential Use as a Biomarker for Atherosclerotic Cardiovascular Diseases - Kengo Sato; Rena Watanabe; Fumiko Itoh; Masayoshi Shichiri; Takuya Watanabe (International Journal of Hypertension, 2013)
Human salusin-α and salusin-β are related peptides produced from prosalusin. Bolus injection of salusin-β into rats induces more profound hypotension and bradycardia than salusin-α. Central administration of salusin-β increases blood pressure via release of norepinephrine and arginine-vasopressin. Circulating levels of salusin-α and salusin-β are lower in patients with essential hypertension. Salusin-β exerts more potent mitogenic effects on human vascular smooth muscle cells (VSMCs) and fibroblasts than salusin-α. Salusin-β accelerates inflammatory responses in human endothelial cells and monocyte-endothelial adhesion. Human macrophage foam cell formation is stimulated by salusin-β but suppressed by salusin-α. Chronic salusin-β infusion into apolipoprotein E-deficient mice enhances atherosclerotic lesions; salusin-α infusion reduces lesions. Salusin-β is expressed in proliferative neointimal lesions of porcine coronary arteries after stenting. Salusin-α and salusin-β immunoreactivity have been detected in human coronary atherosclerotic plaques, with dominance of salusin-β in macrophage foam cells, VSMCs, and fibroblasts. Circulating salusin-β levels increase and salusin-α levels decrease in patients with coronary artery disease. These findings suggest that salusin-β and salusin-α may contribute to proatherogenesis and antiatherogenesis, respectively. Increased salusin-β and/or decreased salusin-α levels in circulating blood and vascular tissue are closely linked with atherosclerosis. Salusin-α and salusin-β could be candidate biomarkers and therapeutic targets for atherosclerotic cardiovascular diseases.